How to Prevent Student Mental Health Problems in Metaverse Era? - Muslihati, Muslihati; Hotifah, Yuliati; Hidayat, Wahyu Nur; Sobri, Ahmad Yusuf; Valdez, Anabelie V.; Ilmi, Achmad Miftahul; Saputra, Nur Mega Aris (Jurnal Kajian Bimbingan dan Konseling, 2024)
Metaverse, a combination of social media, gaming, and virtual reality technology innovation, is a new concept that has attracted the attention of various groups. This concept has also aided numerous groups of people, including the academician. As Metaverse offers various means to innovate, it is projected to change human lives and patterns of interaction. However, Metaverse also presents a number of negative impacts on mental health, even greater than the impacts of online games. This literature review aims to examine the impacts of the Metaverse on adolescents. Then, it develops the relevant preventive strategy through school guidance and counseling programs. This study is motivated by the lack of research related to the impact of Metaverse on adolescents’ mental health and intervention strategies. By applying the PRISMA steps, the study was conducted on scientific articles published from 2017 to 2022 extracted using Publish or Perish software. From the data collection process, we garnered and analyzed 25 relevant articles from ScienceDirect, SpringerLink, Sage Journals, Google Scholar, WoS, ProQuest, Taylor & Francis Group, Emerald Insight, DOAJ, and Garuda. Our analysis results showed that Metaverse potentially has negative impacts on adolescents, especially on non-cognitive aspects, such as social skills, empathy, self-esteem, self-control, and self-regulated learning. In addition, a basic guidance and counseling strategy using various approaches and techniques is required, particularly group guidance using information technology and social media to develop youth literacy about mental health in this metaverse era.